Genetics evaluation of tick resistance in South African Bonsmara cattle - Budeli, Mutshinya Ananias (University of Limpopo (Turfloop Campus), 2010)
The objectives of the study were to estimate genetic parameters for tick resistance and to evaluate the effect of the level of tick infestation on the estimates of genetic parameters in South African Bonsmara cattle. Field data of repeated tick count records (n = 11 280) on 1 176 animals were collected between 1993 and 2005 by ten breeders participating in the National Beef Recording and Improvement Scheme. The distribution of tick count records were normalized using a Box-Cox transformation. Data were divided into 7 sub-data sets based on the mean tick count per contemporary group, to facilitate the investigation of the effect of level of tick infestation on the derived genetic parameters. A repeatability animal model including the fixed effects of contemporary group and age of animal at tick counting and random effects of the direct additive genetic, permanent environmental and residual effects was used to estimate genetic parameters using REML procedures. The additive genetic variances for tick count ranged from 0.01 to 0.08. Variances for the permanent environment ranged from 0.00 to 0.03. Phenotypic variance decreased with increasing mean tick count level while additive genetic variance increased with increasing mean tick count level. The heritability also increased with mean tick count level until a mean tick count level of ≥30. The highest heritability estimate obtained in the current study was 0.17 for data with mean tick count level ≥25. These results suggest that sufficient genetic variation for tick count exists in the Bonsmara cattle. Therefore genetic selection for tick resistance is feasible even though genetic progress may be slow.
Thesis (M.Sc. (Agric.)) --University of Limpopo, 2010
Keywords: Ticks resistance to insecticides -- South Africa; South African bonsmara cattle; 632.9; Ticks -- South Africa; Ticks control -- South frica